Mortgage Lending in Korea : An Example of a Countercyclical Macroprudential Approach - Chang, Soon-taek (2012)
Regulatory regimes are actively discussing macroprudential policy. Korea pursued a countercyclical macroprudential approach to prevent the overheating of mortgage lending and to minimize the risk of loan default. The Korean financial supervisory authority made adjustments in response to both the condition of the housing market and trends in mortgage loans. The lessons learned from the Korean experience are applicable to other situations. First, regulations regarding loan-to-value and debt-to-income ratios and other restrictions on mortgage lending can be employed as an important part of a countercyclical framework. Next, measures need to be applied in a timely manner and according to the specific conditions of each country. Finally, authorities should preemptively prepare macroprudential instruments before banks enter a period of rapid mortgage lending to avoid reckless mortgage lending operations and weaken any speculative motive in the housing market.